Phân tích đồng thời Sb(III) và Sb(V) sử dụng kỹ thuật chiết pha rắn và phổ hấp thụ nguyên tử - hiđrua hóa - Ngọc Anh, Nguyễn Thị; Thảo, Tạ Thị (Vietnam Journal of Chemistry, 2016)
In this study, solid phase extraction techniques were used to separate the two forms separately Sb(V) and Sb(III) anion exchange resin Lewatit by M500, then quantified by spectrometry forms HG-AAS. Survey conditions of M500 static exchanges with Sb(III), Sb (V) showed that Sb(V) completely ion exchange with M500, Sb(III) capable of ion exchange with effective M500 > 95 % HCl 2 M in acidic, balanced exchange reached after 3.5 hours. When technical application to separate solid phase extraction form Sb(III) and Sb(V) inorganic resin M500 uses dynamic method shows the optimal speed is loaded samples 1.5 ml/min, the concentration ratio Sb(III)/Sb(V) greater than 1000 times will reduce the possibility of separating Sb(V) from Sb(III). Eluent used is 0.1 M hydrochloric acid at a rate of 2 ml / min can be completely elution of Sb(III) retained on the solid phase extraction column with a recovery efficiency of over 80 %. Finally, we have successfully applied above method on the real sample